Synthesis and Characterization of ZnO Nanoparticles - Ts, Enkhtuya; G, Tsermaa; G, Batdemberel; P, Munkhbaatar; Sh, Chadraabal; N, Javkhlantugs (Scientific transaction of the National University of Mongolia. Physics, 2022)
This study is focused on hydrothermal synthesis method of zinc oxide nanoparticles by using ammonia and zinc chloride. Synthesized nanoparticles have been characterized by using Xray Diffraction, UV-vis and Photon Cross Correlation (PCCS) spectroscopies, TEM analysis. ZnO thin films were prepared by spin coating method from the solution of ZnO nanoparticles. XRD peak corresponds to hexagonal structure with cell parameter a=0.326 nm and c=0.522 nm. The grain size of zinc oxide nanoparticles has been determined 43.3 nm using the Scherrer formula. As a result of PCCS measurement, synthesized zinc oxide nanoparticles have the mean diameter of ~96 nm of main particles with particle size distribution range of from ~90 nm to ~99 nm. As the result of TEM, the respective size of nanoparticles was around ~96 nm. ZnO nanoparticles were coated on glass and indium-tin oxide (ITO) substrates. The photocatalytic activities were studied ITO substrates with ZnO thin film. ZnO thin films were used as catalyst for reaction Cr(VI) into Cr(III).